"Neoclassical Architecture in Spanish Colonial America: A Negotiated Modernity". Issue 3 (March 2014) - Niell, Paul
Abstract The neoclassical style in Spanish Colonial architecture in the Americas emerged in the late 18th century under the impact of the reforms of the Bourbon monarchy. While subdued ornament, strict geometry, and Greco‐Roman revival motifs characterize this style internationally, few studies examine neoclassical architecture's translation in the Spanish Americas. Scholars such as Manuel Toussaint, George Kubler, and Jean Charlot have associated the Royal Academy of San Carlos with neoclassicism and a shifting away from prevalent baroque aesthetics. Yet neoclassicism's interplay with previous baroque idioms in the Spanish Americas calls into question its functions in colonial society, its reception by period audiences, and local impacts on international forms. Furthermore, the specific roles that neoclassicism played in projects of imperial reform and its negotiation by American societies requires revisionist approaches to the topic.